Organizational Characteristics Affecting the Readiness of Transportation Businesses to Transition from Internal Combustion Engine Heavy Trucks to Electric Trucks - พรภัทรารัตน์, ชาญวิทย์; ธนาบวรพาณิชย์, ณัฐภัสสร; จารุจิตติพันธ์, พิศมัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) examine the readiness of transportation businesses to transition from large internal combustion engine (ICE) trucks to electric trucks, and 2) compare the readiness of transportation businesses based on organizational characteristics. The sample consisted of 400 large truck transportation operators in the Bangkok Port and Laem Chabang Port areas, selected using simple random sampling. The statistical methods used for data analysis included percentage, mean, standard deviation, one-way ANOVA, and pairwise comparison using the LSD method.           The results revealed that: 1) the overall readiness of transportation businesses to transition from ICE trucks to electric trucks was at a high level. When considering each aspect, technological readiness, process adaptation readiness, and personnel readiness were at high levels, while infrastructure readiness and financial and investment readiness were at moderate levels. 2) The comparison based on organizational characteristics indicated that registered capital, number of employees, and number of trucks did not significantly affect the level of readiness. However, business operation duration significantly influenced overall readiness. Additionally, the number of trucks significantly affected process adaptation readiness, whereas financial and investment readiness and infrastructure readiness showed no statistically significant differences.